Analysis Of Unsafe Action And Unsafe Condition Based On Occupational Health And Safety Reporting Programs - Yuliana, Lina; Ardhyaksa, Dhanar (Universitas STRADA Indonesia, 2019)
Background: Accident in the workplace can result in injury or serious damage. This is due to the awareness of the safety of our workers is still very low, so the need for Occupational Health and safety programs in the company is based on existing activities in a company. The level of Occupational Health and safety program activities is determined based on the level of risk and danger in the situation. The greater the risk, the more control is needed on the work done to prevent and control the number of accidents. The Occupational Health and safety Department of PT Pupuk Kaltim has implemented several programs related to work accident prevention, including near miss report and We Care Card Reporting. This program is an Occupational Health and safety program in the form of a reporting system and recording of unsafe conditions and behavior that are at work by involving all employees. Objective: This study aims to determine how effective the We Care Card Reporting program is in reducing accidents. Method: This research is an descpriptive qualitative study. The Information obtained from primary and secondary data which conducted by observation and interview technique. Research Subjects are workers, supervisors and managers there. The Number of accident rate and we care card repoting will be analyze by researcher with the observation data obtained. Result: The comparison before the implementation of the We Care Card Reporting program and after the We Care Card Reporting program there is a reduction in the number of work accidents by 20%. With this reduction in accidents the We Care Card Reporting program cannot be said to be effective. A program classified to the effective in carrying out its functions must obtain a value of at least 60%. But in its routine as a program that has the aim of civilizing workers in Occupational Health and safety culture, this program shows a very high level of participation from workers. Conclusion: We Care Card Reporting be able to reduce the accident number, the ammount is only 20%.